Investigating the Geographical Distribution of Patients with Covid-19 in Mashhad Based on the Recapture Method and Application of Geographic Information Systems - Rostam Saberifar (Kerman University of Medical Sciences, 2020)
Investigating the Geographical Distribution of Patients with Covid-19 in Mashhad Based on the Recapture Method and Application of Geographic Information Systems Saberifar Rostam1* 1. Associate Professor in Urban Planning, Department of Urban Planning, Faculty of Social Sciences, Payame Noor University, Tehran, Iran *Correspondind Author: Rostam Saberifar Address:  Moallem 71, Moallem Blvd., Mashhad, Iran Tel: 00985138683900                                         Email: saberifar@yahoo.com  Abstract: Background & Objectives: Coronavirus has now affected almost all countries in the world and most cities in Iran, and given its numerous consequences, understanding how the virus is distributed and spread can help both discover the treatment methods and return to normal life. To this end, the present study aimed to assess the status of neighborhoods and urban areas of Mashhad and determine the areas least and most affected by this threat. Methods: This descriptive-analytical study was conducted cross-sectionally in the spring of 2020 in thirteen districts of Mashhad Municipality, using field survey and information provided by 300 users who had been trained for this purpose. The data collection tool was an online web-based questionnaire compatible with smartphones. Data were analyzed and mapped using Geographic Information Software (ArcGIS 10.7). Results: Comparison of real field data with those published in cyberspace and unofficial networks showed that the number of infected people was higher in certain parts of the city and high-risk areas were not exactly the same areas identified by cyberspace users. Conclusion: If a system is designed with the ability to officially provide information about the concentration of those infected with the virus to everyone, the people's lives will be brought back to normal conditions sooner and the health authorities will also be assisted in their mission.   Keywords: Corona Virus, Risk Zoning, Geographic Information Systems, Recapture Method   Citation: Saberifar R. Investigating the Geographical Distribution of Patients with Covid-19 in Mashhad Based on the Recapture Method and Application of Geographic Information Systems. Journal of Health Based Research 2020; 6(1): 25-38. [In Persian]